Melflufen or pomalidomide plus dexamethasone for patients with multiple myeloma refractory to lenalidomide (OCEAN): a randomised, head-to-head, open-label, phase 3 study. Issue 2 (February 2022) - Schjesvold, Fredrik H; Dimopoulos, Meletios-Athanasios; Delimpasi, Sosana; Robak, Pawel; Coriu, Daniel; Legiec, Wojciech; Pour, Luděk; Špička, Ivan; Masszi, Tamas; Doronin, Vadim; Minarik, Jiri; Salogub, Galina; et al.
Summary: Background: Melphalan flufenamide (melflufen), an alkylating peptide-drug conjugate, plus dexamethasone showed clinical activity and manageable safety in the phase 2 HORIZON study. We aimed to determine whether melflufen plus dexamethasone would provide a progression-free survival benefit compared with pomalidomide plus dexamethasone in patients with previously treated multiple myeloma. Methods: In this randomised, open-label, head-to-head, phase 3 study (OCEAN), adult patients (aged ≥18 years) were recruited from 108 university hospitals, specialist hospitals, and community-based centres in 21 countries across Europe, North America, and Asia. Eligible patients had an ECOG performance status of 0–2; must have had relapsed or refractory multiple myeloma, refractory to lenalidomide (within 18 months of randomisation) and to the last line of therapy; and have received two to four previous lines of therapy (including lenalidomide and a proteasome inhibitor). Patients were randomly assigned (1:1), stratified by age, number of previous lines of therapy, and International Staging System score, to either 28-day cycles of melflufen and dexamethasone (melflufen group) or pomalidomide and dexamethasone (pomalidomide group). All patients received dexamethasone 40 mg orally on days 1, 8, 15, and 22 of each cycle. In the melflufen group, patients received melflufen 40 mg intravenously over 30 min on day 1 of each cycle and in the pomalidomide group, patients received pomalidomide 4 mg orally daily on days 1 to 21 of each cycle. The primary endpoint was progression-free survival assessed by an independent review committee in the intention-to-treat (ITT) population. Safety was assessed in patients who received at least one dose of study medication. This study is registered with ClinicalTrials.gov, NCT03151811, and is ongoing. Findings: Between June 12, 2017, and Sept 3, 2020, 246 patients were randomly assigned to the melflufen group (median age 68 years [IQR 60–72]; 107 [43%] were female) and 249 to the pomalidomide group (median age 68 years [IQR 61–72]; 109 [44%] were female). 474 patients received at least one dose of study drug (melflufen group n=228; pomalidomide group n=246; safety population). Data cutoff was Feb 3, 2021. Median progression-free survival was 6·8 months (95% CI 5·0–8·5; 165 [67%] of 246 patients had an event) in the melflufen group and 4·9 months (4·2–5·7; 190 [76%] of 249 patients had an event) in the pomalidomide group (hazard ratio [HR] 0·79, [95% CI 0·64–0·98]; p=0·032), at a median follow-up of 15·5 months (IQR 9·4–22·8) in the melflufen group and 16·3 months (10·1–23·2) in the pomalidomide group. Median overall survival was 19·8 months (95% CI 15·1–25·6) at a median follow-up of 19·8 months (IQR 12·0–25·0) in the melflufen group and 25·0 months (95% CI 18·1–31·9) in the pomalidomide group at a median follow-up of 18·6 months (IQR 11·8–23·7; HR 1·10 [95% CI 0·85–1·44]; p=0·47). The most common grade 3 or 4 treatment-emergent adverse events were thrombocytopenia (143 [63%] of 228 in the melflufen group vs 26 [11%] of 246 in the pomalidomide group), neutropenia (123 [54%] vs 102 [41%]), and anaemia (97 [43%] vs 44 [18%]). Serious treatment-emergent adverse events occurred in 95 (42%) patients in the melflufen group and 113 (46%) in the pomalidomide group, the most common of which were pneumonia (13 [6%] vs 21 [9%]), COVID-19 pneumonia (11 [5%] vs nine [4%]), and thrombocytopenia (nine [4%] vs three [1%]). 27 [12%] patients in the melflufen group and 32 [13%] in the pomalidomide group had fatal treatment-emergent adverse events. Fatal treatment-emergent adverse events were considered possibly treatment related in two patients in the melflufen group (one with acute myeloid leukaemia, one with pancytopenia and acute cardiac failure) and four patients in the pomalidomide group (two patients with pneumonia, one with myelodysplastic syndromes, one with COVID-19 pneumonia). Interpretation: Melflufen plus dexamethasone showed superior progression-free survival than pomalidomide plus dexamethasone in patients with relapsed or refractory multiple myeloma. Funding: Oncopeptides AB